Molecular Epidemiology and Risk Factors of Clostridium difficile ST81 Infection in a Teaching Hospital in Eastern China - Yang, Ziyu; Huang, Qian; Qin, Juanxiu; Zhang, Xiaoye; Jian, Ying; Lv, Huiying; Liu, Qian; Li, Min (Frontiers in Cellular and Infection Microbiology, 2020)
Background The prevalence of Clostridium difficile causes an increased morbidity and mortality of inpatients, especially in Europe and North America, while data on C. difficile infection (CDI) are limited in China. Methods From September 2014 to August 2019, 562 C. difficile isolates were collected from patients and screened for toxin genes. Multilocus sequence typing (MLST) and antimicrobial susceptibility tests by E-test and agar dilution method were performed. A case group composed of patients infected with sequence type (ST) 81 C. difficile was compared to the non-ST81 infection group and non CDI diarrhea patients for risk factor and outcome analyses. Results The incidence of inpatients with CDI was 7.06 cases per 10,000 patient-days. Of the 562 C. difficile isolates, ST81(22.78%) was the predominant clone over this period, followed by ST54 (11.21%), ST3 (9.61%), and ST2 (8.72%). Toxin genotype tcdA+tcdB+cdt- accounted for 50.18% of all strains, while 29.54% were tcdA-tcdB+cdt- genotypes. Overall, no isolate was resistant to vancomycin, teicoplanin or daptomycin, and resistance rates to meropenem gradually decreased during these years. Although several metronidazole-resistant strains were isolated in this study, the MIC values decreased during this period. Resistance rates to moxifloxacin and clindamycin remained higher than those to the other antibiotics. Among CDI inpatients, longer hospitalization, usage of prednisolone, suffering from chronic kidney disease or connective tissue diseases and admission to emergency ward 2 or emergency ICU were significant risk factors for ST81 clone infection. All-cause mortality of these CDI patients was 4.92%(n=18), while the recurrent cases accounted for 5.74%(n=21). The 60-day mortality of ST81-CDI was significantly higher than non-ST81 infected group, while ST81 also accounted for most of the recurrent CDI cases. Conclusion This study revealed the molecular epidemiology and risk factors for the dominant C. difficile ST81 genotype infection in eastern China. Continuous and stringent surveillance on the emerging ST81 genotype needs to be initiated.